Instability of magneto-hydro-dynamic flow of thermocapillary liquid layers of shear-thinning nanofluids with oxide nanoparticles in water. (August 2021) - Hussain, Zakir; ur Rehman, Asad; Shaikh, Ahson Jabbar; Hu, Kai-Xin; Ali, Mehboob; Sultan, Faisal; Shahzad, Muhammad; Altanji, Mohamed
Abstract: Nanofluids are the diluted interruptions of nano-sized particles in base fluid such as oil, ethylene glycol, water etc. Nanofluids have wide applications in industries because of their enhanced thermal properties. In present article, the stability analysis of MHD (Magneto-hydro-dynamic) Poiseuille flow of thermocapillary liquid layers of shear thinning nanofluids with oxide nanoparticles in base fluid (water) by imposing transverse magnetic field are studied. The oxide nanoparticles of Aluminum oxide ( Al 2 O 3 ), copper oxide ( CuO ), graphene oxide ( GO ), Iron oxide ( Fe 3 O 4 ), and titanium oxide ( TiO 2 ) are used. Numerical method used in current work is "cheybeshev collocation method". To finding the eigenvalues from generalized Orr-sommerfeld equations, an algorithm named "QZ (Qualitat and Zuverlassigkeit)" used. The stability of different oxide nanoparticles based water nanofluids are compared and discussed through graphs. It has been found that Iron oxide based water nanofluid flow has more destabilizing effect and graphene oxide based water nanofluid flow has more stabilizing effect as compared to other oxide nanoparticles.